2015
DOI: 10.1016/j.str.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure of EspB from the ESX-1 Type VII Secretion System and Insights into its Export Mechanism

Abstract: Graphical Abstract Highlights d The crystal structure of EspB reveals a fused PE/PPE homology domain d EspB has a stabilized bipartite secretion signal that targets the EccCb1 ATPase d EspB oligomerizes to form a ring-shaped heptamer d A model of the heptamer was fit to EM density and crosslinking data In Brief Mycobacterium tuberculosis exports virulence factors to its surface using the ESX-1 secretion system, progressing the infection of human macrophages. Solomonson et al. show that one of these factors, Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 63 publications
7
104
2
Order By: Relevance
“…A recent structural study of EspB, an M. tuberculosis protein secreted by the ESX-1 type VII secretion system, revealed that this protein adopts a conformation similar to that of the PE25/PPE41 structure and forms ring-shaped multimers (54). PE19 and its PPE partner(s) may form similar multimers that localize to the cell wall and influence its permeability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent structural study of EspB, an M. tuberculosis protein secreted by the ESX-1 type VII secretion system, revealed that this protein adopts a conformation similar to that of the PE25/PPE41 structure and forms ring-shaped multimers (54). PE19 and its PPE partner(s) may form similar multimers that localize to the cell wall and influence its permeability.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study provides a better understanding of ESX-specific substrates and lays the groundwork for characterization of EspB and MycP 1 functions in the context of ESX secretion. While this manuscript was under review, Solomonson et al reported crystal structure of Mycobacterium smegmatis EspB homolog (Solomonson et al, 2015). The structures of M. tuberculosis and M. smegmatis EspB display the same fold (2.1–2.3 Å r.m.s.d.…”
Section: Discussionmentioning
confidence: 99%
“…TIC110 is a component of the chloroplast protein import complex (24). EspB from Mycobacterium tuberculosis and LegC3 from Legionella pneumophila are bacterial effector proteins causing phagosome rupture or preventing phagosome fusion with lysosomes, respectively, after uptake into the host cell (25,26). The Bro1V domain is part of the yeast Bro1 protein which is homologous to the human Alix (ALG-2-interacting protein X) protein.…”
Section: Ndgd1 Is Essential For Dgdg Mobilization From the Oem To Thementioning
confidence: 99%